The preventive turn in criminal law - Carvalho, Henrique (Oxford : Oxford University Press, 2017)
Engaging with the dominant contemporary literature on criminal law, prevention, risk, security and criminalisation, this text deploys a theoretical perspective developed through a critical analysis of both classical and contemporary works of social and political theory. It reveals that the pervasiveness of prevention in 21st century criminal justice systems represents not only the consequence of new and unprecedented features of contemporary politics and society, but also the manifestation of essential aspects of the liberal legal and political tradition.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 9, 2017).
Keywords: Punishment in crime deterrence; Criminal justice, Administration of; True Crime; Social services & welfare, criminology